Nonfinancial employment commitment among Muslims and Jews in Israel: examination of the core–periphery model on majority and minority groups. Issue 1 (29th July 2020) - Sharabi, Moshe; Shdema, Ilan; Abboud-Armaly, Oriana
Abstract : Purpose: The Nonfinancial employment commitment (NFEC) of Muslims in general, and of Arab Muslims in particular, has not yet been studied. Accordingly, the purpose of this study is to fill this gap by exploring the NFEC among Arab Muslims in Israel and comparing it to that of Jews in Israel. Design/methodology/approach: The most common indicator of NFEC is the classic "Lottery Question, " which asked whether an individual would continue or stop working if they won a lottery or inherited a large sum of money. The sample included 215 Muslims and 898 Jews representing the Israeli labor force. Findings: The findings reveal higher NFEC among Arab Muslims, particularly among women, compared to Jews. Muslims and Jews in urban areas have a lower NFEC then those who live in smaller localities. Among both Jews and Muslims, NFEC significantly increases with education level and income. Social implications: NFEC is an important measure of the work ethic. A high NFEC of Arab Muslims, especially among women, reflects a high nonactualized potential for Western societies integrating Arab Muslim immigrants and refugees into the labor market. Originality/value: The authors adapted the core–periphery model and found that it could explain the authors' findings regarding NFEC differences among ethnoreligious groups in different residential areas. As the authors indicated before, it is the first time that NFEC of Arab Muslims has been studied.